Des Moines Water Works Leads the Way in Energy Management. Issue 7 (1st September 2022) - Oscarson, Douglas; Corrigan, Ted
Key Takeaways: As with its other operational areas, Des Moines Water Works manages energy consumption—a top expense—by pursuing organization‐wide commitment and maximum efficiency. The utility identified inefficient equipment and processes that were not evident until individual metering and in‐depth analysis had been performed. ISO 50001 provides guidance and best practices to manage energy, improve energy efficiency, and reduce carbon emissions.